An Anomalous Velocity Neutral Hydrogen Structure Near the Galactic Center - Mirabel Miquele, Igor Félix (1975)
An extensive concentration of neutral hydrogen has been observed in the fourth galactic quadrant, with a mean radial velocity of +44 km s−1 referred to the local standard of rest. At a distance ofR kpc from the Sun this structure would contain 2.5×104R2 solar masses of neutral hydrogen.